Technique for modified transantral orbital decompression for improved cosmesis in stable thyroid eye disease. Issue 11 (November 2021) - Lu, J.E.; Bergman, M.; Burnstine, M.A.
Abstract: Functional and aesthetic rehabilitation of exophthalmos in stable thyroid eye disease (TED) can be achieved with a variety of surgical approaches. This article illustrates modifications of the classic transantral technique to provide a graded orbital decompression and achieve improved cosmesis. A retrospective chart review was performed of stable TED patients who elected to undergo the modified transantral decompression; illustrative cases are described. This modified transantral orbital decompression allows for graded orbital decompression surgery, adding to the range of treatment options for stable TED patients.